2019
DOI: 10.1016/j.rpor.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a volumetric-modulated arc therapy (VMAT) single phase prostate template as a class solution

Abstract: Aim: To assess a class solution template for volumetric-modulated arc therapy (VMAT) for prostate cancer using plan analysis software.Background: VMAT is a development of intensity-modulated radiotherapy (IMRT) with potential advantages for the delivery of radiotherapy (RT) in prostate cancer. Class solutions are increasingly used for facilitating RT planning. Plan analysis software provides an objective tool for evaluating class solutions. Materials and methods:The class solution for VMAT was based on the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…VMAT plans were generated using a 6 MV photon beam, with the clinical Monaco Version 5.11.01 TPS (Elekta AB, Stockholm, Sweden) and the Agility MLC. For all patients included in this study a VMAT plan using two coplanar arcs was calculated using a Monte Carlo algorithm, with a calculation grid size of (0.3 cm) 3 and a statistical uncertainty during dose prediction of 1%. These plans were delivered clinically.…”
Section: Vmatmentioning
confidence: 99%
See 1 more Smart Citation
“…VMAT plans were generated using a 6 MV photon beam, with the clinical Monaco Version 5.11.01 TPS (Elekta AB, Stockholm, Sweden) and the Agility MLC. For all patients included in this study a VMAT plan using two coplanar arcs was calculated using a Monte Carlo algorithm, with a calculation grid size of (0.3 cm) 3 and a statistical uncertainty during dose prediction of 1%. These plans were delivered clinically.…”
Section: Vmatmentioning
confidence: 99%
“…The low-field MR-linac system generates a 6 MV flattening-filter-free (FFF) photon beam in the presence of a 0.35 T magnetic field, using the RayZR MLC, a double-stacked and double-focused 138-leaf MLC with 4.15 mm effective leaf-width at isocentre. The dose calculation algorithm is also based on Monte Carlo simulation, with a calculation grid size of (0.3 cm) 3 and a statistical uncertainty during dose prediction of 1%.…”
Section: Imrt Mrlmentioning
confidence: 99%
“…“Impossible DVH (red)” is defined as the DVH generated using the minimum dose that an off‐target voxel must receive given 100% target coverage. Studies that used the PlanIQ TM software have reported improvements in the treatment plan quality 8–13 . Recently, PlanIQ TM was integrated into Autoplan®, which is implemented in Pinnacle and has been clinically applied 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Some work has been done in developing class solutions for the treatment of prostate with IMRT, 11,13 even in case of particularly challenging anatomical situations, as in the case of bilateral hip prostheses, 14 and VMAT, for both conventional fractionation 15,16 and SBRT. 17,18 These studies demonstrated automated planning for prostate cancer is feasible and can produce plans that are at least as good as manual plans.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of class solutions allows for the "bias-free" comparison between different techniques by applying the previously established templates. 15 Class solutions have been used for technique comparison in breast treatment, 19,20 while a five-field IMRT template was established and evaluated on 40 patients treated with accelerated partial breast irradiation for left and right lesions. 21 The developed template was demonstrated to produce highly conformal and consistent treatment plans.…”
Section: Introductionmentioning
confidence: 99%